Multi-omics analysis identifies PPARα as a key inhibitor of hepatocyte ferroptosis in sepsis-associated liver injury - Shi-Ling He; Jian-Chuan Lin; Gao-Fang Wu; He-fan He (PLoS ONE, 2026)
Background Sepsis-associated liver injury (SLI) increases the risk of death in septic patients, and a primary pathological alteration in sepsis is ferroptosis in the liver. However, the specific mechanism of its occurrence remains largely unclear. Our work is to validate key pathways connected with ferroptosis in SLI and elucidate potential pharmaceutical targets involved in this process. Methods To confirm targets related to SLI, we screened three SLI microarray datasets (GSE23767, GSE40180 and GSE104342) from the GEO database and obtained the ferroptosis-related differentially expressed genes (FRDEGs). A functional enrichment analysis of FRDEGs was performed. The protein–protein interaction network was used to visualize the interactive relationship of FRDEGs. Additionally, the potential biological functions and enrichment pathways of FRDEGs were elucidated through GO and KEGG analysis. Furthermore, we obtained the single-cell dataset (GSE238000) from liver tissue from GEO database to determine the series of cell subtype mainly expressing target molecules. Finally, we performed a serial of in vivo and in vitro experiments to further validate the findings of bioinformatic analysis. Results A total of 51 genes that are expressed differently in SLI involve ferroptosis. These genes are involved in negative regulation of apoptotic process, the endoplasmic reticulum, and identical protein binding. The KEGG pathway study revealed that they were mainly involved in the PPAR signaling pathway. Among three isoforms of PPAR family, PPARα is most abundant in the liver. We then observed that it was significantly downregulated in hepatic tissue of SLI mice and PPARα agonist WY-14643 effectively blocked sepsis-induced hepatic ferroptosis. Subsequently, single-cell analysis demonstrated that PPARα is predominantly expressed in hepatocytes, which was downregulated in LPS-treated THLE-2 cells. Notably, consistent with the in vivo results, PPARα activator WY-14643 also significantly alleviated LPS-induced ferroptosis in THLE-2 cells. Conclusion The validation of ferroptosis-related pathway PPARα in this study greatly deepens our understanding of the potential mechanism of SLI, and provide promising therapeutic targets for the disease.